Analysis of Space Circulation in Raya Ganting Mosque, Padang City - M. Bima Pebrimdesdi; Cut Azmah Fithri; Yenny Novianti (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
Raya Ganting Mosque is the oldest mosque in Padang City and has a role in social and religious life. The mosque has special rules related to circulation, such as avoiding meetings between males and females, which disturbs the sanctity of worship. The circulation of space in the mosque must be considered for the convenience of worshipers, where the issue in this study is still the occurrence of cross circulation in the foyer, left side entrance, and the prayer room which is closer to the entrance to the women's ablution room. This study aims to analyze the suitability of the existing space circulation in the Mosque using the theory of D. K Ching (1993). The method in this research uses the Descriptive Qualitative Method by using variables of building access, Circulation flow configuration, and relationship between space and road. The results showed that the circulation space based on the achievement of the mosque building has more than one entrance access, the flow of motion of worshipers in the mosque is accessed linearly, and the relationship between spaces has a spatial relationship through space, ends in space, and penetrates in space. In conclusion, the circulation of space in the Mosque is effective and efficient, where the achievement of the building has more than one entrance to avoid congestion of worshipers, the flow of movement of worshipers in the mosque is accessed linearly which makes it easier for worshipers to go to each room in the mosque, and the relationship between spaces through space and ends in space where good minimize cross-circulation between worshipers. However, some aspects such as the arrangement of the women's ablution room must be considered to reduce cross-circulation between worshipers, thereby increasing the effectiveness of the comfort of worshipers in worship. Keywords: Space Circulation, Cross-Circulation, Raya Ganting Mosque